Adsorption of Pb (II) ions from aqueous solutions using carbon nanotubes: A systematic review. (1st April 2021) - Vesali-Naseh, Masoud; Vesali Naseh, Mohammad Reza; Ameri, Pegah
Abstract: The presence of Pb (II) ions, as a major pollutant source, in the water resources causes global health concerns. The adsorption method has been conventionally used for the determination and removal of Pb (II) ions. In this systematic review, all the adsorption-based studies during 1991–2020, which have used carbon nanotubes (CNTs) as the adsorbent of Pb (II), were reviewed and those qualifying the related requirements were selected for more evaluation. The experimental conditions including pH, temperature, initial concentration, adsorbent dosage, ionic strength, and contact time as well as adsorbent regeneration and adsorption capacity/recovery were extracted. Almost all of the included papers carried out adsorption experiments at room temperature and showed that the higher temperature leads to a higher adsorption rate. More than 47.0% of included studies assigned the optimum pH at 6–7, and reported that a higher pH leads to the metal precipitation. Moreover, the increase of initial concentration improved the adsorption capacity whereas it leads to the decrease of metal ion recovery. Most of the articles (42.2%) have fitted the Langmuir isotherm model, which reveals that the Pb (II) uptake on the CNT surface is a homogenous and monolayer process. Using isotherm behavior, the thermodynamic parameters (i.e. ΔG°, ΔH°, and ΔS°) were calculated in 19.8% of included studies and the results denoted the spontaneous process for Pb (II) adsorption. Furthermore, about 42.6% of included studies have described the adsorption kinetic by the pseudo-second-order model and suggested the chemisorption as the rate-limiting step. Consequently, the review results revealed that CNT composites are promising adsorbents for Pb (II) uptake from aqueous solutions. Graphical abstract: Image 1 Highlights: Systematic review of all adsorption-based studies for Pb removal using CNT adsorbents. Extraction of optimum environmental conditions. Evaluation of isotherm models, kinetic mechanisms, and thermodynamic data.